THE INFLUENCE BETWEEN INJECTABLE PLATELET-RICH FIBRIN AND PLATELET-RICH PLASMA TOWARDS GINGIVAL FIBROBLAST CELL PROLIFERATION - Danastri, Arifia Anindita; Suryono, Suryono; Murdiastuti, Kwartarini (Faculty of Dentistry, Universitas Islam Sultan Agung, 2021)
ABSTRACTBackground: Gingiva is the outermost periodontal tissue that acts as a mechanical and biological barrier to the root of the teeth and alveolar bone. The main cellular elements in the gingiva are fibroblasts. Fibroblast cell proliferation is an important process in tissue regeneration. Growth factors that can stimulate fibroblast cell proliferation can be found in regenerative agents, such as injectable platelet-rich fibrin (i-PRF) and platelet-rich plasma (PRP). The aim of this study was to examine the influence between i-PRF and PRP on the gingival fibroblast cell proliferation in vitro study on primary cell culture.Method: Gingival fibroblast cell were obtained from primary cell culture derived from healthy gingiva. Ten mL of peripheral blood were centrifuged for i-PRF and PRP preparation. The samples were divided into three groups: i-PRF, PRP, and fibroblast cells without treatment. Cell proliferation were observed at day 1, day 3, day 5 using MTT assay at 550 nm. The data were analyzed by Two-Way ANOVA test, followed by Post Hoc test.Result: The results showed that the cell proliferation increased from day 1, 3, and 5 in all groups. The absorbance value of the cell proliferation in order from highest to lowest: i-PRF, PRP, and cell control.Conclusion: i-PRF and PRP increased the gingival fibroblast cell proliferation. i-PRF increased the cell proliferation higher than PRP.